2005
DOI: 10.1007/s11060-004-1366-2
|View full text |Cite
|
Sign up to set email alerts
|

A study of sequential high dose cyclophosphamide and high dose carboplatin with peripheral stem-cell rescue in resistant or recurrent pediatric brain tumors

Abstract: The MTD of carboplatin with stem-cell rescue is 700 mg/m2/day for 3 days. Sequential stem-cell supported cyclophosphamide and carboplatin was tolerable in children with brain tumors and produced responses in PNETs and Germinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Two-year survival rates for relapsed medulloblastoma were reported to be below 20% (8). Recently, sequential cycles of dose-intensive chemotherapy or tandem transplantation have been tried in the treatment of chemo-sensitive high-risk or recurrent brain tumors, including recurrent medulloblastoma (9-11). The survival rate was reported as a broad range, 5-54%, by studies done in various different situations with regard to pre-transplant conventional chemotherapy, conditioning regimens, disease status prior to HDCT, and adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-year survival rates for relapsed medulloblastoma were reported to be below 20% (8). Recently, sequential cycles of dose-intensive chemotherapy or tandem transplantation have been tried in the treatment of chemo-sensitive high-risk or recurrent brain tumors, including recurrent medulloblastoma (9-11). The survival rate was reported as a broad range, 5-54%, by studies done in various different situations with regard to pre-transplant conventional chemotherapy, conditioning regimens, disease status prior to HDCT, and adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study by Cheuk et al reported that 5 patients with PR disease status before HDCT, who had a median 8-month disease free period, did not survive a long-term (12, 14). However some researchers suggest that using multiple sequential intensive therapy or tandem transplantation has some benefit in this disease status before HDCT, because a single application of HDCT cannot eradicate the disease (9). Sung et al (10) reported that of 9 patients with PR status before HDCT, whose tumors were high-risk or relapsed medulloblastoma and supratentorial primitive neuroectodermal tumor, 8 who received tandem transplantation were alive with a median follow-up of 18 month and 7 of those were disease free.…”
Section: Discussionmentioning
confidence: 99%
“…After detailed review of those 31 articles, only 11 of them fulfilled the inclusion criteria ( Fig. 1; Table 1) [16][17][18][19][20][21][22][23][24][25][26]. Four out of eleven studies were prospective series, none of them was a randomized controlled trial.…”
Section: Included Studiesmentioning
confidence: 99%
“…The median duration of tumor response was 10 months (range: 1.5–87 months), with two children disease-free at 66 and 87 months. Actuarial survival was only 21% (Foreman et al, 2005). That said, chemotherapy has vastly improved the outlook for children with medulloblastoma and has afforded delay of institution of radiation therapy in infants with brain tumors, decreasing somewhat the toxic effects of radiation to the developing brain (Gottardo and Gajjar, 2008).…”
Section: Brain Tumorsmentioning
confidence: 99%